The Relationship Between Family Support, Health Worker Support, and Mothers' Attitudes Towards Exclusive Breastfeeding at the Telukjambe Community Health Center, Karawang Regency, in 2025 - Hapipah Nur Auliah; Sudiono Sudiono; Saleh Budi Santoso (INDOGENIUS, 2026)
Background & Objective: Exclusive breastfeeding is the provision of breast milk alone without any additional complementary food or drink from birth to 6 months of age. The success of exclusive breastfeeding is influenced by various factors, including family support, health worker support, and maternal attitudes. This study aims to determine the relationship between family support, health worker support, and maternal attitudes towards exclusive breastfeeding at the Telukjambe Health Center, Karawang Regency, in 2025. Method: This study used an analytic design with a cross-sectional approach. The sample amounted to 91 respondents who were selected using purposive sampling technique. The statistical test used was Chi-Square along with the Odds Ratio (OR) at a significance level of p < 0.05. Result: The results showed a significant relationship between family support (p = 0.000, OR = 49.038 CI = 10.267-234.234), health worker support (p = 0.000, OR = 8.944, CI = 3.104-25.774), and maternal attitude (p = 0.000, OR = 15.897, CI = 4.798-52.672) towards exclusive breastfeeding. Conclusion: Mothers with less support or negative attitude were significantly more likely to not provide exclusive breastfeeding. Therefore, it is recommended to increase promotional and educational efforts regarding the importance of family support, the active role of health workers, and the formation of positive attitudes in mothers, in order to optimize exclusive breastfeeding coverage.